Coordination of Open Access to research publications in Sweden - Eellend, Beate (Septentrio Conference Series, 2017)
Watch the VIDEO here. The Swedish Government’s direction for the next ten-year research policy, as set out in the Swedish Research Bill from 2016, includes the goal that scientific publications which are the result of publicly funded research should be made immediately open access on publication. As of 2017 the National Library of Sweden holds an appropriation directive from the Swedish Government to act as a national coordinating body in the work towards a transition to open access to scholarly publications. The Government states that all stakeholders have a common responsibility in fulfilling this objective and that clear incentives and mechanisms are needed in order to encourage researchers to publish their research output immediately open access. A number of obstacles to a transition to an open access publishing system have been identified by the Swedish Research Council in their Proposal for National Guidelines for Open Access to Scientific Information (2015). Based on this, the National Library of Sweden initiates and coordinates five studies to be conducted during 2017-2019. The five studies are: The current merit and resource allocation system versus incentives for open access Funding for a transition from a subscription-based to an open access publishing system Open access to scholarly monographs Financial and technical support for converting peer-reviewed and scholarly journals from toll access to open access Monitoring of compliance with open access policies and mandates Representatives from all main stakeholders with a key role in the national transition to an open access publishing system will participate in one working group for each study. This includes HEI’s, research funders and researchers. The studies will result in further recommendations to the Government on how to nationally solve the identified obstacles. The work will be coordinated and facilitated by the National Library of Sweden.